Do investors’ reactions to environmentally friendly news announcements differ across industries? A comparative analysis of Japan’s food and automotive industries - Murashima, Miho (Journal of Business Economics and Management, 2022)
Recently, investors’ growing awareness of environmental concerns has prompted many businesses to implement green policies and procedures. Investors’ reactions to firms’ environmental efforts vary across different industries. However, few empirical studies have addressed these differences, especially in Japan – the third-largest sustainable investor in the world. Using data from Japanese food and automotive industries, this research examined sector-specific differences in investors’ reactions to firms’ environmental performance, indicated by environmentally friendly news releases, using a short-term event study and Student’s t-tests. Results indicated that investors respond negatively to environmental activities in the food and automobile sectors, supporting neo-classical theory. The data also imply that, in Japan, industry variances have a neutral effect on short-term performance but a significant long-term effect. In addition, long-term investor responses to environmentally friendly news in the food sector are more unfavorable than in the automobile industry. This study has implications for policymakers and managers.